Analysis of land cover change due to deforestation at Holiday Resort Nature Park, North Sumatra Province, Indonesia - Daulay, Ulil Amri; Ahmad, Alfan Gunawan; Purwoko, Agus (Talenta Publisher, 2023)
. Deforestation activities in Indonesia are increasingly becoming a real concern. All of these actions resulted in the loss of 50% of the world's tropical forests, impacting the livelihoods of forest-dependent people. Changes in land cover are common in natural resource use areas. Land change is an important issue for planners and policymakers. One of them is the encroachment of the Holiday Resort Nature Park (HRNP) area of North Sumatra Province, which is a form of forest governance and weak law enforcement. Especially in this area, there are Sumatran elephants (Elephas maximus sumatranus), which are classified as critically endangered species. Analysis of land cover change can be used as material for formulating policies. By utilizing the Geographic Information System (GIS), it will be easier to analyze land cover and land use changes. The purpose of this study was to analyze land cover changes due to deforestation at HRNP. Spatial analysis of cover change using imagery and testing the accuracy of deforestation data, land cover satellite imagery, and verification in the field. The results showed that during the past 30 years, there has been deforestation from secondary dryland forest of 2079.3 ha to forest, namely swamp shrubs covering an area of 30.5 ha (1.5%) and non-forest covering an area of 2048.8 ha (98.6%). The highest deforestation rate occurred from 1996 to 2000 as much as 2027.3 ha (97.5%). The form of land cover due to deforestation is plantations 1990.8 ha (95.7%) and land cover forms 57.8 ha (2.8%). The conclusion shows that deforestation was triggered by weak law enforcement from the beginning until now, thus providing a more realistic opportunity for communities to encroach